TEACHING UZBEK AS A FOREIGN LANGUAGE TO MEDICAL STUDENTS IN UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Challenges in teaching Uzbek as a second language have been discussed, and some solutions have been provided in this article. Moreover, the number of foreign students has been increasing at Tashkent Medical Academy. This encourages the development of teaching Uzbek as a second language.